2020
DOI: 10.3390/app10030913
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Evolution of Drought Characteristics in Balochistan, Pakistan

Abstract: In the wake of a rapidly changing climate, droughts have intensified, in both duration and severity, across the globe. The Germanwatch long-term Climate Risk Index ranks Pakistan among the top 10 countries most affected by the adverse effects of climate change. Within Pakistan, the province of Balochistan is among the most vulnerable regions due to recurring prolonged droughts, erratic precipitation patterns, and dependence on agriculture and livestock for survival. This study aims to explore how the character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…For instance, Khan et al (2020) provided an understanding and potential of drought prediction models in Pakistan by machine learning techniques (Khan et al 2020). Jamro et al (2020) explored the Standardized Precipitation Evapotranspiration Index (SPEI) based Spatio-temporal variability of drought characteristics in Balochistan province as well as in the entire region of Pakistan (Jamro et al 2019;Jamro et al 2020). Qaiser et al, (2021) presented a study about the evaluation of seasonal droughts using a composite drought index in Northern Punjab.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Khan et al (2020) provided an understanding and potential of drought prediction models in Pakistan by machine learning techniques (Khan et al 2020). Jamro et al (2020) explored the Standardized Precipitation Evapotranspiration Index (SPEI) based Spatio-temporal variability of drought characteristics in Balochistan province as well as in the entire region of Pakistan (Jamro et al 2019;Jamro et al 2020). Qaiser et al, (2021) presented a study about the evaluation of seasonal droughts using a composite drought index in Northern Punjab.…”
Section: Introductionmentioning
confidence: 99%
“…The SPI [33] showed a negative trend in Baluchistan from 1975 to 2010 [34]. A study that used SPEI found that the Baluchistan region had a negative SPEI value, indicating the intensified drought during 1902-2015 [35]. Ghani et al (2018) concluded that SPI exhibited a significant negative trend in Balakot and a positive trend in Parachinar using met station data [36].…”
Section: Introductionmentioning
confidence: 99%
“…The province is facing a limited amount of precipitation along with considerable changes in temperature (Naz et al 2020). If these conditions prolong, it can make this land extremely prone to severe droughts shortly (Ashraf and Routray 2013;Jamro et al 2020). Total annual precipitation is meager, owing to dry summer (Zahid and Rasul 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Impacts of changing climate make the arid region of the province more vulnerable to frequently witnessed seasonal droughts (Jamro et al 2020 ). An increase in surface temperature coupled with low average rainfalls is likely to cause seasonal shifts and disturb weather parameters (Ashraf and Routray 2015 ; Naz et al 2020 ; Yokomatsu et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%